Enhancing Student Engagement through Wordwall-Based Interactive Learning in Vocational School - Jatmika, Surya; Oktaviani, Nawang; Pratiwi, Indah; Sari, Dhany Efita; Susilo, Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study focuses on how learning with Wordwall-based interactions can increase the activity and enthusiasm of students in the Sharia Banking Accounting subject at SMK Negeri 1 Klaten. In such learning, the use of traditional and limited media has led to lower participation, decreased motivation, and inadequate learning achievements.Methodology: A qualitative case study approach was used with participants consisting of 45 students from classes XII AKL 1 and XII AKL 3, along with one accounting teacher. Data collection used classroom observations, semi-structured interviews, and documentation of learning activities. Data analysis followed the interactive model involving data condensation, data display, and conclusion drawing. Triangulation methods and sources were used to increase data credibility.Results: The inclusion of Wordwall, mainly in the form of multiple-choice quiz games, resulted in a significant increase in student engagement, as demonstrated by increased observable activeness by 17.7% from 75.6% to 93.3%. Students manifested increased activity, collaborative interaction, and intrinsic motivation. The use of game-based digital media also succeeded in creating a more enjoyable learning environment and reduced passive learning behavior.Applications/Originality/Value: This paper provides empirical evidence for the pedagogical advantages of game-based learning media in vocational education. Wordwall proved to be an effective tool for boosting active engagement and improving learning experiences. The results emphasize the potential of digital interactive platforms in supporting technology-enhanced and AI-ready learning ecosystems, in line with current educational agendas of digital transformation.